1989
DOI: 10.1159/000293486
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Thyroxine-Binding Globulin in Pre-Eclampsia

Abstract: Plasma concentrations of thyroxine (T4) and thyroxine-binding globulin (TBG) as well as triiodothyronine uptake (T3U) were measured in 32 proteinuric pre-eclamptic patients and 24 normotensive pregnant women at similar gestations in the third trimester. The pre-eclamptic patients had slightly lower TBG, and significantly lower T4, concentrations, which were significantly correlated. They also had significantly lower infant birth weight which was correlated to the TBG and T Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As TBG concentration is reported to be lower in unsuccessful pregnancies [17], this decrease may be a useful indicator of placental function deteriora tion in pregnancy [5], We think that the placental dys function may cause failure in estrogen production, there fore decrease in TBG, TT3 and TT4 and simultaneously growth failure to the fetus. We found a significant correla tion between birth weight and maternal TBG levels which was similar to that of Lao et al [5].…”
Section: Bw -Ft 4imentioning
confidence: 80%
See 4 more Smart Citations
“…As TBG concentration is reported to be lower in unsuccessful pregnancies [17], this decrease may be a useful indicator of placental function deteriora tion in pregnancy [5], We think that the placental dys function may cause failure in estrogen production, there fore decrease in TBG, TT3 and TT4 and simultaneously growth failure to the fetus. We found a significant correla tion between birth weight and maternal TBG levels which was similar to that of Lao et al [5].…”
Section: Bw -Ft 4imentioning
confidence: 80%
“…as well as high TSH concentration tended to have low-birth weight babies. Lao et al [5] suggested that the reduced serum concen trations of thyroid hormones in toxemia may in part be explained by the loss of protein and hence protein-bound hormones in the urine. The infant birth weight was found to be related to the maternal serum albumin level in situa tions where there was heavy proteinuria such as the nephrotic syndrome [10], In normal pregnancy, the increasing production of pla cental estrogen during pregnancy stimulates the hepatic synthesis of TBG [11][12][13][14][15], and this is reflected by a decrease in T3U [16].…”
Section: Bw -Ft 4imentioning
confidence: 99%
See 3 more Smart Citations